One case of double-stage orthodontic treatment of skeletal Class Ⅱ combined with impacted teeth - GUO Kai, HAN Xinying, MA Haojie, LIU Lijuan, YANG Fanghong (Kouqiang yixue, 2024)
Patients with skeletal Class Ⅱ often show symptoms such as protrusion of maxillary anterior teeth, mandibular retraction, open lips and teeth, deep overbite, and deep overjet, which seriously affect the facial appearance. This article reports a case of an adolescent male patient with skeletal Class Ⅱ combined with impacted teeth treated by one-stage early correction and two-stage fixation. After treatment, the patient’s skeletal Class Ⅱ symptoms improved significantly, including the improvement of mandibular retraction. The problem of open lips and teeth was solved; the facial appearance tended to be straight, and there was no obvious abnormality of the temporomandibular joint. This case shows that early correction can achieve good therapeutic effects on this kind of patients and can avoid or reduce the possibility of orthognathic surgery for these patients in adulthood.